2013
DOI: 10.1093/cid/cit411
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Antifungal Treatment Improves Health Status in Patients With Chronic Pulmonary Aspergillosis: A Longitudinal Analysis

Abstract: Antifungal therapy improved health status and prevented CPA progression in most patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 32 publications
4
68
0
1
Order By: Relevance
“…The significant predilection to CPA is in agreement with the findings of recent studies in Iran which demonstrated that CPA is the most common clinical presentation of aspergillosis in individuals with healed tuberculosis (35). Importantly, patients with CPA require long-term maintenance antifungal therapy to improve symptoms and prevent the recurrence of infection (36,37). The acquisition of azole resistance in A. fumigatus is an emerging public health problem which definitely needs continued surveillance at the national and international levels (9).…”
Section: Discussionsupporting
confidence: 86%
“…The significant predilection to CPA is in agreement with the findings of recent studies in Iran which demonstrated that CPA is the most common clinical presentation of aspergillosis in individuals with healed tuberculosis (35). Importantly, patients with CPA require long-term maintenance antifungal therapy to improve symptoms and prevent the recurrence of infection (36,37). The acquisition of azole resistance in A. fumigatus is an emerging public health problem which definitely needs continued surveillance at the national and international levels (9).…”
Section: Discussionsupporting
confidence: 86%
“…Azole drugs are frequently used prophylactically, sometimes for long periods of time, to prevent Aspergillus infections, as well as to treat these infections (1,13). In addition, agricultural azoles are routinely used to control plant fungal pathogens (5).…”
mentioning
confidence: 99%
“…For CPA, long-term antifungal treatment is usually required, but case-by-case surgery should be discussed [41]. Patients with poor pulmonary function are generally inoperable and can, alternatively, undergo endovascular treatment such as bronchial artery embolisation (BAE) in the case of life-threatening haemoptysis and also receive systemic antifungal therapy [42].…”
Section: Cpa: Current Treatment Optionsmentioning
confidence: 99%
“…In a very recent randomised controlled trial, Agarwal et al [31] reported the superiority of itraconazole therapy over standard supportive treatment. Two other trials have also shown an improvement in quality of life after initiating triazoles in the setting of CPA [41,55]. While several different classes of antifungal agents have been introduced, the emergence of triazole antifungal drugs has been found to be an effective therapeutic agent against almost all forms of CPA [48].…”
Section: Cpa: Current Treatment Optionsmentioning
confidence: 99%